Diseño e implementación de una máquina de control numérico por computadora (CNC) de tres ejes para la fabricación de placas de circuito impreso (PCB). (2022)
This paper presents the design and implementa tion of a computer numerical control (CNC) machine for the manufacture of printed circuit boards (PCB), which is proposed to encourage the development of design and manufacturing skills. PCB's, which are important in various professional areas of electroni As a result, is obtained c engineering. a CNC machine with physical characteristics of 380mm wide, 310mm deep and 270mm high, its work area supports circuit boards no larger than 280mm x 130mm; As hardware, the integrated circuit 'Atmega328P' is used, which is assembled to the control board. Finally, a practical operating guide is developed with which it is intended to instruct on the handling of the machine.